Evaluasi Kualitas Shopeepay Menggunakan ISO/IEC 25010 - Bithia Insoraki Rumabar; Evi Maria (Diponegoro University, 2024)
This research aims to evaluate the quality of Shopeepay using ISO/IEC 25010 from the user side, namely Satya Wacana Christian University students. Evaluation of the quality of Shopeepay needs to be done because the high level of use of Shopeepay is also followed by increasing user complaints. This research assesses eight characteristics: functional suitability, reliability, performance efficiency, usability, security, compatibility, maintainability, and portability. There were 140 respondents in this research. This research uses a quantitative descriptive approach, and data is analyzed by calculating the total score for each characteristic regulated in ISO/IEC 25010. The results of the Shopeepay quality evaluation found that functional suitability is 79%, performance efficiency is 75 percent, compatibility is 74 percent, usability is 78 percent, and reliability is 77 percent, security 83 percent, maintainability 76 percent, and portability 78 percent. The quality of Shopeepay is considered very good from a security perspective, and the rest is good. The lowest score is on the compatibility aspect, so system developers and Shopee management need to improve the compatibility of this application because payment transactions and top-up balances fail due to this aspect.